2022
DOI: 10.1177/17568277221093848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shear-coaxial injector hydrodynamics on high-frequency combustion instabilities in a representative cryogenic rocket engine

Abstract: The excitation mechanism of a thermoacoustic instability in a 42-element research rocket thrust chamber with representative operating conditions with respect to European cryogenic rocket engines is investigated in detail. From previous research it was known that the chamber 1T mode can be excited by persistent heat release rate oscillations which are modulated by the resonant modes of the liquid oxygen injectors. The excitation source of the longitudinal injector eigenmodes is investigated in this study. Fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…In previous studies, the flow dynamics inside injector elements with orifices have been reported as the excitation source of the combustion instability under certain conditions. High-frequency (HF) instabilities of liquid oxygen/hydrogen (LOX/H 2 ) combustion were observed when the resonance mode of the LOX-post matched the first transverse acoustic mode (1T) in the combustion chamber of the research thrust chamber model 'D' (or "BKD") [2][3][4] as shown in Figure 1. Armbruster et al [3] concluded that the orifice whistling phenomenon at a Strouhal number of approximately 0.35 caused the excitation of the acoustic eigenmodes in the LOX injectors, which modulated the heat release rate, leading to an excitation of the 1T mode of the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the flow dynamics inside injector elements with orifices have been reported as the excitation source of the combustion instability under certain conditions. High-frequency (HF) instabilities of liquid oxygen/hydrogen (LOX/H 2 ) combustion were observed when the resonance mode of the LOX-post matched the first transverse acoustic mode (1T) in the combustion chamber of the research thrust chamber model 'D' (or "BKD") [2][3][4] as shown in Figure 1. Armbruster et al [3] concluded that the orifice whistling phenomenon at a Strouhal number of approximately 0.35 caused the excitation of the acoustic eigenmodes in the LOX injectors, which modulated the heat release rate, leading to an excitation of the 1T mode of the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies in the past indicated a strong effect of the hydrogen temperature on the stability margins [4] of a rocket combustor. A recent study [5] assessed the role of hydrodynamic effects, e.g., vortex shedding, behind shear coaxial injectors that may also lead to a modulation of the heat release rate in the combustion chamber. Another possible instability mechanism that has been observed in rocket combustion chambers [6], as well as air-breathing combustion systems (cf.…”
Section: Introductionmentioning
confidence: 99%